THE FIGHT AGAINST BREAST CANCER: AN EXPERIENCE REPORT - Guedes de Almeida, Leticia; Silva Oliveira, Geane; de Lira Silva, Macerlane; José Oliveira do Nascimento Gomes, Francisco; Barros de Quental, Ocilma (Health and Society, 2024)
This article reports the experience of a 60-year-old woman, living in a low-income community, who faced a battle with breast cancer. Initially, the disease was neglected and treated with home remedies, but when she sought medical help, she was diagnosed with advanced breast cancer. Despite medical recommendations, the patient chose not to undergo conventional treatment, following only palliative care. Family support played a crucial role in her decisions, influencing her choice to refuse surgery. However, the patient eventually withdrew from medical care, highlighting the need for a holistic approach and ongoing support for patients in similar situations. This report highlights the importance of raising awareness about breast cancer, early detection and adequate medical monitoring, as well as the need for emotional and psychological support for patients and their families throughout the treatment process.